Outcome of adult proximal humerus locking plate in the treatment of paediatric subtrochanteric fractures - Chetia, Naba Pallab; Medhi, Himashis; Das, Manasjyoti; Bidyananda, Aritra (International Journal of Research in Orthopaedics, 2019)
Background: Subtrochanteric fractures in children are treated by different conservative and operative methods. Patient’s age may be the single most important factor deciding treatment. Several studies have documented superior results with internal fixation compared to non-operative treatment. The aim of the study is to evaluate the outcome of proximal humerus locking plate fixation of subtrochanteric femoral fractures in children. Methods: Between October 2015 and December 2017, 13 children with closed subtrochanteric femoral fractures including 3 pathological fractures were treated in our tertiary care teaching institute and the results were retrospectively analysed. Children of both sexes within 5–12½ years of age with isolated subtrochanteric fractures were included. There was no open fracture and fracture associated with neuromuscular disease or any systemic injury. In all cases, ORIF with proximal humerus locking plate was done using lateral approach. Results: Average age at the time of injury was 9.35 years (range 5–12 ½ years). There were four (30.77%) short oblique, four (30.77%) long oblique, three (23.08%) transverse fractures and two (15.38%) comminuted fractures. Average operative time was 88.76 minutes and average intra operative blood loss was 86.23 ml. Average follow-up was 13 months. All fractures showed radiological union at an average of 8 weeks. One case had superficial infection which was controlled by antibiotics. Two patients had limb lengthening (average 0.75 cm) but required no intervention. Conclusions: Internal fixation with adult proximal humerus locking plate appears as a good treatment option for paediatric subtrochanteric femoral fractures.